PENDIDIKAN MULTIKULTURAL DAN IMPLIKASINYA TERHADAP KEBIJAKAN PENDIDIKAN - Mufidah, Luk-Luk Nur (LPPI Universitas Al-Qolam Malang, 2016)
Multicultural education is one of the alternatives to integrate diversity in Indonesia. Multicultural education and implementation is a strategy based on the concept of diversity that exists in society, particularly that of the learners, either in the form of ethnic, cultural, language, religion, social status, age, gender, or capabilities. With multicultural education that teaches the values of tolerance and togetherness more intensively, students are expected to not only be able to absorb the lessons learned, but also to have awareness to always behave humanist, pluralist and democratic. It is also expected that learners will appreciate all the differences that exist and regard it as a wonderful blend of life. Keywords: Pendidikan Multikultural, kebijakan pendidikan